To a question of legal support of participation of the Republic of Kazakhstan in foreign economic activity and the international economic relations (Journal of actual problems of jurisprudence, 2019)
In given article some questions of legal maintenance of participation of Republic Kazakhstan in foreign trade activities and theinternational economic relations are considered. The author analyzes problems of interaction of norms of the international and nationalright, main principles of the international cooperation.